Pemanfaatan Limbah Organik Perkebunan dan Feses Domba Garut Menjadi Pupuk Organik Cair di Desa Ciputri Kecamatan Pacet, Cianjur - Mulyanto, Naufal Rafa; Assajad, Zacky Nurrohman; Antika, Tiara; Madja, Muhammad Daffa Nurhadi Suryadi; Rifaldo, Akhmad; Azzahra, Nabilah Putri Fatimah; Faadhila, Intan Hanifa; Zahrani, Alifia Sasky; Hilwan, Iwan (Jurnal Pusat Inovasi Masyarakat, 2025)
Liquid Organic Fertilizer (POC) is a processed fertilizer resulting from the fermentation of organic materials, usually made from a mixture of agricultural and livestock waste. It is easy to apply, does not require a large amount, and the nutrient content that can be directly utilized by plants is an advantage of POC. Based on the dependence of residents on chemical fertilizers, which have a negative impact on the soil, this activity was finally carried out. This activity aims to overcome the problem of unutilized agricultural and livestock waste in Ciputri Village. The implementation of this activity is in Ciputri Village in July 2024, starting with socialization and continuing with a direct demonstration of POC. The results of the implementation of the activity increased public knowledge of POC to 90%. This activity provides new insights for the residents of Ciputri Village regarding the use of agricultural and livestock waste to deal with the problems of chemical fertilizers and waste management.